Comparative analysis of different calculation methods of the Geological Strength Index (GSI) based on qualitative and quantitative approaches (Rudarsko-geološko-naftni zbornik, 2022)
In this research, the dispersion of the Geological Strength Index (GSI) values ​​obtained with quantitative and qualitative approaches has been evaluated in four rock outcrops of different geomechanical quality. The subjective component associated with qualitative or visual methods has been studied by conducting a virtual survey in a group of forty participants constituted by civil engineers, geological engineers, and mining engineers from Peru, Spain, and Chile, who were given a data sheet with the photograph and the basic description of each rock mass, the results showed that the GSI values fit a normal distribution characterized by a mean value and a standard deviation, which in some cases could present moderate to high coefficients of variation (COVs). This paper also includes the study of the dispersion of the GSI values ​​obtained with quantitative formulations that have been evaluated and incorporated into regional databases to assess trends, mainly in the GSI-RMR' relationships. The results indicate that the average GSI values ​​reported with both approaches are similar; however, with the quantitative methodologies, COV values ​​were classified as low to moderate, which is better adjusted to the suggested COV values for the GSI. Despite this, quantitative methodologies must be used with caution, taking into account the characteristics of the rock masses on which the relationships have been defined.